Contemporary Empirical Methods in Software Engineering 2020
DOI: 10.1007/978-3-030-32489-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Benefitting from the Grey Literature in Software Engineering Research

Abstract: Researchers generally place the most trust in peer-reviewed, published information, such as journals and conference papers. By contrast, software engineering (SE) practitioners typically do not have the time, access or expertise to review and benefit from such publications. As a result, practitioners are more likely to turn to other sources of information that they trust, e.g., trade magazines, online blog-posts, survey results or technical reports, collectively referred to as Grey Literature (GL). Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 60 publications
0
25
0
1
Order By: Relevance
“…Hence, we argue that Opinion and Experience papers are also very important to the community of AI engineers. This is a concern being raised by the research community of empirical software engineering, which highlights grey literature as a valuable data source for research [18].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we argue that Opinion and Experience papers are also very important to the community of AI engineers. This is a concern being raised by the research community of empirical software engineering, which highlights grey literature as a valuable data source for research [18].…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we conducted a grounded theory study based on the grey literature [30]. We used formal modeling to precisely encode our findings (similar to [26]).…”
Section: Methodsmentioning
confidence: 99%
“…Grounded Theory (GT) [6], [7] is a systematic research method for 1 See also: https://microservice-api-patterns.org/ [8], [30] is the main data source in our work. In software engineering, grey literature can be defined as "any material about software engineering that is not formally peer-reviewed nor formally published" [30]. We decided to study grey literature sources representing acknowledged practitioners' views on the interrelation of distributed APIs and DDD.…”
Section: Methodsmentioning
confidence: 99%
“…Garousi et al [22][23][24] showed the benefits of complementing Systematic Literature Reviews (SLRs) with grey literature in software engineering research. Software engineering practitioners typically lack the time or expertise to access academic publications; thus, they mainly rely on grey literature to stay up to date and inform their work.…”
Section: Multivocal Literature Reviewmentioning
confidence: 99%